A new method for measuring kinetics and kinematics in field resisted running: comparison to laboratory tethered running - Sousa, F. A. P.; Gobatto, C. A. (ISBS Proceedings Archive (Michigan), 2017)
The current investigation compared results of a resisted sprint device to measure running kinetics and kinematics in the field with those measured by tethered running on a treadmill. Ten male students underwent two sessions comprising two 35m tethered sprints in laboratory or track. Step length and frequency, velocity, force and power were measured for each stride and averaged at each 5m interval. Variables reliability was attested by significant ICC-A between test-retest (between 0.60 and 0.88). Kinematic variables did not present a significant difference (P between 0.09 and 0.72). Despite force and power were systematically higher in laboratory condition (P < 0.001), track condition presented higher correlations between force and velocity at each stride. Track tethered running may be a useful to monitor kinetics and kinematics in track resisted running drills.